Sistema tegumentario del guanaco (Lama Guanicoe) (Veterinary Science, 2017)
Samples of different cutaneous areas of mature gumps were studied, previousl y processed by means of technics for optic microscopy. The differential characteristics among the different areas have observed them in relation to the thickness of the skin in general, to the abundance of the annexed glands and follicles pilosos, and fundamentally to the distribution of these last ones and at your disposal in follicular groups of variable size according to the considered area. It was observed that these groups contained bigger number of follicles in the skrn of the head. In many cases they stood out in these groupings main and secondary follicles
Keywords: Camelid; Gumps; Skin